Implementation of the principles of Cipta, Rasa, Karsa in GC Persada Transportation Company to Improve Service Quality - Billani, Adestya Nindi Salsa; Danda, Made; Faisal, Muhammad Noer; Ketlin, Lidwina Arie Dewannti; Ananta, Berli; Sari, Pristin Prima (International Journal of Community Service (IJCS), 2025)
This research aims to improve service quality at GC Persada Transportation Company, through a socialization-based approach, especially the concept of “Cipta, Rasa, Karsa” from Ki Hajar Dewantara. The community service program involved students and lecturers from Sarjanawiyata Tamansiswa University who optimized the service system through the Spereadsheet application to improve service quality. The methods used include socialization, training and implementation of Spereadsheet digital technology to maximize recording according to customer wishes to reduce the occurrence of miscommunication with other employees. The results showed that the approach of implementing digital technology on employees is significant to improve the quality of service that is more professional and effective.